Math, asked by taniishusaikh, 1 year ago

If m and n are zeroes of the polynomial x2-x-6, then find a quadratic polynomial whose zeroes are (3a+2b) and (2a+3b).

Answers

Answered by knjroopa
8

Answer:

Step-by-step explanation:

Given If a and b are zeroes of the polynomial x2-x-6, then find a quadratic polynomial whose zeroes are (3a+2b) and (2a+3b).

Since a and b are zeroes of polynomial of the equation x^2 – x - 6 we have

Sum = a + b = -b/a = - (- 1)/1 = 1

Product = ab = c/a = - 6/1 = - 6

Sum = 3 a + 2 b + 2 a + 3 b

Sum = 5(a + b) = 5

Product = (3 a + 2 b)(2 a + 3 b)

            = 6 a^2 + 4 ab + 9 ab + 6 b^2

         = 6 (a^2 + b^2) + 13 ab

So we have the polynomial as

 6((a +b)^2 - 2 ab) + 13 ab

 6(a + b)^2 - 12 ab + 13 ab

6(a +b)^2 + ab

6(1)^2 + 1(-6)

6 - 6 = 0

The equation is x^2 - 5 x = 0

Answered by amitnrw
5

Answer:

x² - 5x = 0

Step-by-step explanation:

If a and b are zeroes of the polynomial x2-x-6, then find a quadratic polynomial whose zeroes are (3a+2b) and (2a+3b).

a & b are roots of x²-x-6

a + b = -(-1)/1  = 1  (sum of roots)

ab =-6/1 = -6    ( product of roots)

3a + 2b  & 2a + 3b are roots

so sum of roots =  5a + 5b = 5(a +b) =  5 (1) = 5

Product of roots = (3a + 2b)(2a + 3b)

= 6a² + 6b² +  13ab

= 6((a + b)² - 2ab)) + 13ab

= 6 (a + b)² + ab

= 6(1)² + (-6)

= 6 - 6

= 0

sum of roots = 5  & Product of roots = 0

Hence Equation  x² - 5x  + 0 = 0

=> x² - 5x = 0

Similar questions